Mit den Waffen des Geistes
This report features an interview with Dzevad Hozo, a Bosnian painter and art historian, in his Sarajevo apartment. Hozo reflects on the ongoing siege of Sarajevo, Bosnia's historic tolerance, and discusses the war's manifestation in Bosnian art as well as his own.